Postdischarge Falls and Readmissions: Associations with Insufficient Vision and Low Health Literacy among Hospitalized Seniors. (1st August 2016) - Jaffee, Ethan G.; Arora, Vineet M.; Matthiesen, Madeleine I.; Hariprasad, Seenu M.; Meltzer, David O.; Press, Valerie G.
Abstract : The role of patient-level risk factors such as insufficient vision has been understudied. Because insufficient vision may interfere with health literacy assessments, the full impact of low health literacy among older patients with impaired vision is unknown. We sought to determine whether senior inpatients' insufficient vision and low health literacy are associated with adverse outcomes postdischarge, specifically falls and readmissions. We conducted an observational study of adult medicine inpatients at an urban hospital. Visual acuity and health literacy were screened at bedside. Outcomes data were collected by telephone 30 days postdischarge. Among 1, 900 participants, 1, 244 (65%) were reached postdischarge; 44% had insufficient vision and 43% had low health literacy. Insufficient vision was associated with postdischarge falls among participants ≥65 years (adjusted odds ratio [AOR] 3.38, 95% confidence interval [CI] 1.42–8.05), but not among participants <65 years (AOR 1.44, 95% CI 0.89–2.32). Low health literacy was associated with readmissions among participants ≥65 years (AOR 3.15, 95% CI 1.77–5.61), but not among participants <65 years (AOR 0.78, 95% CI 0.56–1.09). The results suggest the need to implement screening for older inpatients' vision and health literacy. Developing effective interventions to reduce these risks is critical given national priorities to reduce falls and readmissions.